Exploring the Underpinnings and Longitudinal Associations of Word Reading and Word Spelling: A 2-year Longitudinal Study of Hong Kong Chinese Children Transitioning to Primary School. (2nd January 2022) - Ye, Yanyan; Yan, Mengge; Ruan, Yijun; McBride, Catherine; Zheng, Mo; Yin, Li
ABSTRACT: We investigated the correlates of word reading and spelling as well as the relations of word reading and spelling in Hong Kong Chinese children. A set of literacy-related skills and delayed copying were administered in kindergarten, and Chinese word reading and dictation were tested at kindergarten as well as in first and second grade. The final preferred model in cross-lagged analysis showed that reading performance at kindergarten and first grade predicted spelling performance at first grade and second grade, respectively. However, the relations were not bidirectional. This study underscores the critical roles of morphological awareness, RAN, and delayed copying for early literacy performance in Chinese. In addition, it demonstrates that earlier reading performance predicts later spelling performance in Chinese, but early spelling does not predict subsequent reading in Chinese in the early grades.